2014
DOI: 10.1093/cid/ciu1128
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Micafungin for the Prevention of Invasive Fungal Infection in High-Risk Liver Transplant Recipients

Abstract: In this randomized clinical trial comparing micafungin 100 mg with standard-care antifungal prophylaxis (fluconazole, liposomal amphotericin B, or caspofungin) in high-risk liver transplant patients, micafungin 100 mg was noninferior and had a better kidney safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
46
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 40 publications
9
46
0
4
Order By: Relevance
“…Our result was similar to the incidence reported elsewhere, with rates reaching 17.7% [1,4,15,16,17,18,19,20,21]. In the era of MELD and targeted prophylactic antifungal therapy, our study was able to offer three interesting pieces of information: (i) all patients who developed IFI within two months of LT had one or more risk factors and were receiving antifungal therapy after LT; (ii) the time to onset of IFI in the ICU after LT ranged from five days to 252 days.…”
Section: Discussionsupporting
confidence: 92%
“…Our result was similar to the incidence reported elsewhere, with rates reaching 17.7% [1,4,15,16,17,18,19,20,21]. In the era of MELD and targeted prophylactic antifungal therapy, our study was able to offer three interesting pieces of information: (i) all patients who developed IFI within two months of LT had one or more risk factors and were receiving antifungal therapy after LT; (ii) the time to onset of IFI in the ICU after LT ranged from five days to 252 days.…”
Section: Discussionsupporting
confidence: 92%
“…Fort un et al demonstrated that the prophylactic use of caspofungin for 21 days in liver transplant recipients at high risk for IFD not only was well tolerated but also notably reduced the incidence of this complication (27). More recently, the TENPIN study also reported the noninferiority of micafungin compared with the standard of care in high-risk liver transplant patients, with a more favorable renal safety profile (28). In contrast, most cases of IFD in pediatric patients occurred beyond month 6, once antimold prophylaxis had been stopped (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this high infectious complication rate, there is a paucity of data regarding antibiotic prophylaxis in OLT patients. Several trials have evaluated perioperative antifungal and antiviral prophylaxis . Another trial has assessed the type of antimicrobial prophylaxis; however, there have been no studies comparing surgical prophylaxis duration and rates of postoperative infections in liver transplant patients, highlighting the dearth of evidence surrounding perioperative antibiotic prophylaxis in these patients .…”
Section: Discussionmentioning
confidence: 99%